Uma sequência didática para o ensino de trigonometria no ensino médio - PINHEIRO, Edu Souza (2021)
Trigonometry is the area of mathematics that studies the measures of the sides and angles of a triangle. It is not possible to say precisely when it appeared, however, what is known is that it began in the mid-4th century BC, in great civilizations such as the Egyptian and Babylonian. Trigonometry was seen as an essential tool for calculating measurements, being used in various situations, such as astronomy, surveying, civil construction (where the pyramids stand out in Egypt) and navigation. Despite the mathematical limitations of the time, it was from these first steps that we arrived at modern mathematics and trigonometry. The big question is that trigonometry is an area of complex understanding, so, in order to keep students' attention and interest, it is essential that teachers come to link theoretical classes to everyday human applications. In addition, with the evolution of society and technological innovations, that purely expository teaching methodology is outdated and boring for students. With this, it is essential that the teacher intersperses this type of class with practical classes, lectures, practical exercises, as well as using the aid of technology, so that students can better fix the contents exposed in the classroom. From all this, the objective of this study is to present a didactic sequence for the teaching of trigonometry in high school, which is in accordance with the PCN and the BNCC and at the same time is modern, that is, it is not composed only of classes expository. As a study methodology, the dissertation in question is an exploratory study carried out through bibliographic research. In conclusion, it can be said that trigonometry is essential in society, so the realization of more dynamic classes and the use of a didactic sequence with more modern class methodology can considerably improve the teaching-learning process of this content in the environment. school.